The potential of archaeosomes as carriers of pDNA into mammalian cells - OGAN, AYŞE; TURAN, KADİR (TAYLOR & FRANCIS LTD, 2016)
This paper describes the formulation of archaeosomes and the evaluation of their abilities to facilitate in vitro DNA delivery. Lipids of the H.hispanica 2TK2 strain were used in archaeosome formation, which is formulated by mixing H.hispanica 2TK2 lipids with plasmid DNA encoding green fluorescent protein (GFP) or beta-galactosidase (beta-gal). Archaeosome/pDNA formation and unbound DNA were monitored by agarose gel electrophoresis. The archaeosome formulations were visualized by AFM and TEM. The zeta potential analysis showed the archaeosomes to be electronegative. The composition of archaeosomes and the DNA dose for transient transfection into HEK293 cells were optimized, and the relationship between the structure and activity of archaeosomes in DNA delivery was investigated. By themselves, archaeosomes showed low efficiency for DNA delivery, due to their anionic nature. By formulating archaeosomes with a helper molecule, such as DOTAP, CaCl2, or LiCl, the capability of archaeosomes for gene transfection is significantly enhanced. The transfection profiles of efficient archaeosomes are proved to have a long shelf-life when maintained at room temperature. Thus, the archaeal lipids have the potential to be used as transfection reagents in vitro.
Keywords: gene delivery; lipid extraction; archaeosome; Haloarcula hispanica; in vitro transfection; ORAL DELIVERY; ULTRADEFORMABLE ARCHAEOSOMES; LIPOSOMES; LIPIDS; STABILITY; VACCINE; SYSTEMS; BIOSYNTHESIS; VESICLES